O2.4. ABNORMAL CORTICAL NEURAL OSCILLATIONS UNDERLYING CONTEXT PROCESSING DEFICITS IN SCHIZOPHRENIA AND THEIR BIOLOGICAL RELATIVES. (9th April 2019) - Kang, Seung Suk; III, Angus MacDonald; Shim, Miseon; Ramsay, Ian; Sponheim, Scott
Abstract: Background: People with schizophrenia (SZ) have deficits in context processing (CP), which refers to an executive process that guides adaptive behaviors according to goals and stored contextual information. Similar deficits were also found in their biological relatives, suggesting that CP-related dysfunctions might be endophenotypic markers of schizophrenia that reflect central pathology of the disorder. Abnormal cortical neural oscillations might be the brain mechanisms underlying CP deficits in schizophrenia. However, the precise spatial, temporal, and frequency abnormalities associated with the illness and genetic liability of schizophrenia are largely unknown. Methods: We analyzed high-density electroencephalography (HD-EEG) and functional MRI data collected from 22 SZ, 20 biological relatives of SZ (RSZ), and 30 healthy controls [HC]) during an optimized CP task called stimulus response reversal task (SRRT). ExGaussian reaction time (RT) distribution analysis was used to determine abnormalities in intra-individual RT variability in CP. We identified fMRI cortical regions of interest (ROIs) activated for CP, then the ROI source signals of HD-EEG were computed using individual realistic head models and a source localization algorithm employing boundary element method (BEM). Cohen's class time-frequency (TF) measures of the ROI signals were computed to define accurate time and frequency dynamics of CP-related cortical oscillations in high and low CP (HCP and LCP) load conditions. Results: RSZ were normal in all behavioral performance indices, and SZ were also normal in response accuracy and motor speed (RT-mu). However, SZ had larger response instability (RT-sigma) than HC only in HCP trials, suggesting their specific deficits in contextual motor control. We identified task-related fMRI ROIs including dorsal middle frontal gyrus (dMFG), inferior middle frontal gyrus (iMFG), inferior frontal gyrus (IFG), inferior parietal lobules (IPL), anterior cingulate cortex (ACC), motor cortex (MC), and middle occipital gyrus (mOG) in the both hemispheres. TF analyses of the ROI signals in 3 time-windows of the task trials identified CP-related neural oscillatory activities (HCP-LCP differences) in low-frequency (1–5 Hz) event-related synchrony (LF-ERS) and alpha band (8–12 Hz) event-related desynchrony (A-ERD) that varied across the groups. Unlike HC who had simultaneous LF-ERS increases in dMFG and IPL during contextual cue encoding for HCP trials, SZ and RSZ had LF-ERS increases only in IFG and iMFG respectively. During delay period (maintenance of cue information) in HCP trials, HC had increased LF-ERS in dMFG and IPL, while RSZ had increased LF-ERS in iMFG. In contrast, SZ had A-ERD increases in mOG during delays in HCP trials. The HCP-related RT-sigma increases in SZ were predicted by their CP-related LF-ERS (1–4 Hz) during maintenance (1300–1500 ms after cue onsets) in IPL (r=-.71, p=.002). Before responses to probes in HCP trials where response conflicts should be resolved, HC had LF-ERS increases in dMFG, ACC, and IPL while RSZ had such increases in iMFG, ACC, and MC. In contrast, SZ had increases in pre-response A-ERD for HCP trials in mOG and MC. Discussion: Results suggested that SZ and RSZ had common deficits in LF-ERS of the dorsal prefrontal and parietal network, but they utilized resources of other cortical regions to compensate their core deficits in CP. HCP-specific response instability in SZ might be caused by their parietal dysfunction to update contextual rules and additional ACC-motor dysfunctions. In summary, CP-related deficits in the dorsal prefrontal-parietal network might be the endophenotypic markers of schizophrenia, while ACC-motor cortical deficits might be disease-specific marker unique to SZ.